Cellular localization of low-molecular-weight penicillin-binding proteins and other cell wall remodeling enzymes in Mycobacterium smegmatis - Maphatsoe, Masethabela Maria (My University, 2017)
The majority of bacterial species responsible for the spread of infectious diseases in humans undergo morphological changes enabling them to withstand harsh environmental conditions for survival within host cells. These changes, together with distinct modes of growth, underpin the bacterium’s overall ability to maintain its integrity during infection. Amongst the deadliest infectious diseases worldwide, infection with Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), ranks the highest in terms of mortality. TB has been a scourge in medical history for decades. The rapid emergence of drug-resistant TB strains has necessitated the development of novel, rapid and effective anti-TB therapy. In this regard, the design of anti-TB drugs which can be co-administered with antiretroviral treatment requires a detailed understanding of the processes associated with bacterial cell assembly and cell division. DD-carboxypeptidases (DD-CPases), classified as low-molecular-weight penicillin- binding-proteins (LMW PBPs) have been implicated in the remodelling of peptidoglycan (PG) in the cell wall and are important for cell growth and division. PG remodelling requires tight spatial and temporal regulation to maintain cell wall integrity and cell size/shape. In this study, we assessed localization patterns of an essential DD-CPase, DacB, and non-essential DD-CPases; MSMEG_1661, MSMEG_2432 and MSMEG_2433 in Mycobacterium smegmatis, a non-pathogenic relative of M. tuberculosis. For this, we constructed DD-CPase derivatives fused to a C-terminal green fluorescence protein tag to determine their cellular localization patterns. Using a similar approach, we localized other known cell wall remodelling and cell division proteins, namely PonA2, DivIVA and FtsZ to study their localization relative to DacB in wild-type M. smegmatis and mutants defective for DD-CPases. We observed unique localization patterns for these proteins that offer new insights in remodelling of the mycobacterial cell surface during division. FtsZ is localized to mid-cell, where cell division is initiated, while DivIVA, a division site selection protein, localized to both poles. Interestingly, DacB localized in a similar manner to the essential high-molecular-weight PBP, PonA2, which localized mainly to both poles. In some cases, PonA2 (9 %) and DacB (10 %), also localized to one pole. Next, we localized these proteins in mutants defective for DD-CPases. For this, a mutant defective in MSMEG_2433 and MSMEG_2432 was constructed by site-specific allelic exchange. Using this strain, in addition to other pre-existing mutants, we demonstrated that loss of DD-CPases results in mis-localization of FtsZ and consequently, the division apparatus. We further assessed the MSMEG2433 MSMEG2432 mutant by phenotypic characterization. A growth kinetics analysis showed that this grew comparably similar to the parental wild-type and had marginal defects in biofilm formation. There were no differences in spatial localization of new PG synthesis. Collectively, this study has contributed to an enhanced understanding of PG remodeling in mycobacteria.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Masters of Science in Medicine. July 2017.
Keywords: Mycobacterium smegmatis; Tuberculosis